Whole-genome sequencing of Staphylococcus epidermidis bloodstream isolates from a prospective clinical trial reveals that complicated bacteraemia is caused by a limited number of closely related sequence types. (May 2020) - Shelburne, S.A.; Dib, R.W.; Endres, B.T.; Reitzel, R.; Li, X.; Kalia, A.; Sahasrabhojane, P.; Chaftari, A.-M.; Hachem, R.; Vargas-Cruz, N.S.; Jiang, Y.; Garey, K.; et al.
Abstract: Objectives: The significance of isolating Staphylococus epidermidis from a blood culture is highly heterogeneous, ranging from contamination to an indication of a serious infection. Herein we sought to determine whether there is a relationship between S. epidermidis genotype and clinical severity of bacteraemia. Methods: S. epidermidis bacteraemias from a prospective, multicentre trial at 15 centres in the United States and one in Spain were classified as simple (including possible contamination), uncomplicated, and complicated. Whole-genome sequencing (WGS) was performed on 161 S. epidermidis isolates, and clinical outcomes were correlated with genotypic information. Results: A total of 49 S. epidermidis sequence types (STs) were identified. Although strains of all 49 STs were isolated from patients with either simple or uncomplicated infection, all strains causing complicated infections were derived from five STs: ST2, ST5, ST7, ST16, and ST32. ST2 and ST5 isolates were significantly more likely to cause uncomplicated and complicated bloodstream infections compared to simple bacteraemia (odds ratio 2.0, 95%CI 1.1–3.9, p 0.04). By multivariate regression analysis, having an ST2 or ST5 S. epidermidis bacteraemia was an independent predictor of complicated bloodstream infection (odds ratio 3.7, 95%CI 1.2–11.0, p 0.02). ST2/ST5 strains carried larger numbers of antimicrobial resistance determinants compared to non-ST2/ST5 isolates (6.34 ± 1.5 versus 4.4 ± 2.5, p < 0.001). Conclusion: S. epidermidis bacteraemia was caused by a genetically heterogeneous group of organisms, but only a limited number of STs—particularly multidrug-resistant ST2 and ST5 strains—caused complicated infections.